TRADISI MANAQIBAN SEBAGAI PRAKTIK LIVING HADIS(STUDI PADA MASYARAKAT KAMPUNG ASEM TARIKOLOT, KABUPATEN SERANG, BANTEN) - Albarra Gilang Andika; Anzil Alaina Maidah; Muhammad Alif (CV. Adiba Aisha Amira, 2026)
This study examines the tradition of manaqiban recitation in Kampung Asem Tarikolot, Serang Regency, Banten, as a form of living hadith practice within the religious life of the community. The manaqiban tradition is practiced routinely and continuously; however, it does not originate from textual awareness of the Prophet’s hadith. The community understands manaqiban as a religious practice whose benefits are directly experienced, such as inner tranquility, perceived blessings in life, and the strengthening of social relations among congregants. This research employs a qualitative method with a field research approach through observation and interviews and is analyzed using the living hadith perspective and a structural-functional approach. The findings indicate that hadith values such as consistency in religious practice (istiqamah), reliance upon God (tawakkul), and solidarity among fellow believers are alive and internalized in the practice of manaqiban, even though they are not explicitly recognized by the community as deriving from the Prophet’s hadith. This study affirms that hadith exists not only as a normative text but also as living values that are interpreted and practiced within local Muslim religious traditions